Correction to: General practitioners' and out-of-hours doctors' role as gatekeeper in emergency admissions to somatic hospitals in Norway: registry-based observational study - Jesper Blinkenberg; Sahar Pahlavanyali; Øystein Hetlevik; Hogne Sandvik; Steinar Hunskaar (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.